IT in Educational Administration and Management. CET Information Sheet No. 9 - Monaco, Jenny; MacDonald, Lesley; Council for Educational Technology, London (England). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
This document provides information on the use of information technology (IT) to assist in educational management and administration, considers where future developments may lead, and provides definitions of IT and its elements--information handling, communications technology, and information transformation. The involvement of the Council for Educational Technology (CET) in investigations of the use of IT for helping school administrators and teachers with administrative tasks is described and a number of tasks now being performed by computers are listed. The recommendations resulting from a seminar convened at CET to discuss the organizational, technical, and informational aspects of introducing IT into the schools are provided, and some factors to be considered when purchasing or developing computer-based educational administration and management systems are suggested. Also included are lists of sources for further advice and information; software suppliers; magazines, journals, and books on IT; and institutions currently or recently involved in research. A list of Microelectronics Education Programme (MEP) Regional Information Centres is appended. (DJR)
Availability: Council for Educational Technology, 3 Devonshire Street, London W1N 2BA, England.
Administrators.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Managed Instruction; Computer Software; Developed Nations; Educational Administration; Elementary Secondary Education; Foreign Countries; Information Technology; Management Information Systems; Microcomputers; United Kingdom -- Vendors; Guides, Non-Classroom.; Information Analyses; Reports, Descriptive